Keterbatasan Manajemen Sarana Dan Prasarana Dapat Menunjang Motivasi Belajar Siswa Di MA Raudlatul Istiqomah Suko Maron - Husnah, Rif'atul (Najah: Journal of Research and Community Service, 2024)
The purpose of this study intends to explain the limitations of management of facilities and infrastructure to support student learning motivation at the MA Raudlatul Istiqomah Suko Maron educational institution. Limited facilities and infrastructure can actually have a negative impact on student learning motivation. However, in some cases, these limitations can give rise to factors that encourage student learning motivation. As is the case at the MA Raudlatul Istiqomah educational institution, limitations as a challenge, students can see it as a challenge to remain enthusiastic and try harder in learning. They may feel compelled to overcome obstacles and achieve despite the limited facilities available. Creativity and Innovation Limited facilities and infrastructure often trigger students to become more creative and innovative in their learning approaches. They may seek alternative ways to access resources, utilize available technology, or collaborate with peers to overcome limitations. This process can increase their motivation to learn and achieve their goals. When resources are limited, students may appreciate and make better use of existing resources. They may feel more motivated to make efficient use of available time and facilities, thereby improving the quality and effectiveness of their learning. Limited facilities and infrastructure can encourage students to work together and collaborate in overcoming obstacles. They may help each other, share knowledge, or support each other in achieving learning goals. This solidarity and collaboration can increase students' learning motivation because they feel supported and involved in the learning community. However, it is important to remember that limited facilities and infrastructure are generally considered an obstacle to achieving optimal learning quality. The availability of adequate facilities and infrastructure is an important factor in creating a conducive learning environment and motivating students as a whole. Therefore, efforts must be made to improve and expand educational facilities and infrastructure in order to increase student motivation and quality of learning.